Synthesis and size dependent optical studies in CdSe quantum dots via inverse micelle technique - Hamizi, N.; Johan, M.R. (Elsevier, 2010)
Cadmium selenide quantum dots (CdSe QDs) were successfully synthesized without using trioctylphosphine (TOP). The XRD pattern showed zinc-blend phase of the CdSe QDs. The absorption and PL spectra exhibit a strong blue shift as the QDs size decreases due to the quantum confinement effect. In addition, the quantum efficiency of CdSe QDs with TOP capping is higher than CdSe QDs with oleic acid capping. TEM image shows a spherical shape, compact and dense structure of CdSe QDs. A good agreement between the Tauc's model and experimentally measured absorption spectra of CdSe QDs is achieved. The FTIR peak at similar to 1712 cm(-1) spectra confirms the influence of oleic acid as a capping agent. (C) 2010 Elsevier B.V. All rights reserved.